DISBIOSE INTESTINAL E OBESIDADE INFANTIL: UMA REVISÃO SISTEMÁTICA - Monteiro, João; Santos, Juliana; Silva, Mayana; Gomes, Thaynara; Vieira, Nathalia (Gep News, 2019)
Trabalho apresentado durante o I MASMI